Greek Tragedy and the Contemporary Actor - Dunbar, Zachary (Springer International Publishing, 2018)
This book offers a provocative and groundbreaking re-appraisal of the demands of acting ancient tragedy, informed by cutting-edge scholarship in the fields of actor training, theatre history, and classical reception. Its interdisciplinary reach means that it is uniquely positioned to identify, interrogate, and de-mystify the clichés which cluster around Greek tragedy, giving acting students, teachers, and theatre-makers the chance to access a vital range of current debates, and modelling ways in which an enhanced understanding of this material can serve as the stimulus for new experiments in the studio or rehearsal room. Two theoretical chapters contend that Aristotelian readings of tragedy, especially when combined with elements of Stanislavski's (early) actor-training practice, can actually prevent actors from interacting productively with ancient plays and practices. The four chapters which follow (Acting Sound, Acting Myth, Acting Space, and Acting Chorus) examine specific challenges in detail, combining historical summaries with a survey of key modern practitioners, and a sequence of practical exercises.